Bacillus polyfermenticus Ameliorates Colonic Inflammation by Promoting Cytoprotective Effects in Colitic Mice - Im, Eunok (American Society for Nutrition, 2009)
Although human consumption of Bacillus polyfermenticus provides several health benefits, the probiotic effect of this bacterium against colonic inflammation has not yet, to our knowledge, been studied. Therefore, we induced colitis in mice by oral or intrarectal administration of dextran sodium sulfate (DSS) or trinitrobenzenosulfonic acid (TNBS), respectively, and investigated the effect of B. polyfermenticus on colitis. We found that mice treated with DSS or TNBS along with B. polyfermenticus had reduced mortality and severity of colitis (weight loss, diarrhea, and mucosal damages) than mice treated with DSS or TNBS alone. B. polyfermenticus also reduced the expression of inflammatory molecules, including chemokine (C-X-C motif) ligand 1, intercellular adhesion molecule, and tumor necrosis factor-α, but enhanced the expression of the antiinflammatory cytokine interleukin-10 in the inflamed mouse colon. Moreover, B. polyfermenticus suppressed apoptosis both in vivo in inflamed colonic mucosa and in vitro in colonic epithelial cells stimulated with apoptosis-inducing agents (FasL or Clostridium difficile Toxin A) when the apoptotic response was determined by a terminal deoxynucleotidyl transferase dUTP nick end labeling assay and cleavage of poly(ADP-ribose) polymerase or caspase-3, respectively. Treating colonic epithelial cells with B. polyfermenticus-conditioned medium (BPCM) enhanced cell proliferation and induced the phosphoinositide 3-kinases/Akt signaling pathway, suggesting that this bacterium can promote epithelial cell proliferation. BPCM also promoted the migration of colonic epithelial cells. These data suggest that B. polyfermenticus ameliorates colonic inflammation by suppressing apoptosis and promoting epithelial cell proliferation and migration.